Congenital vascular malformations update - Rendón Elías, Felipe Gerardo; Hernández Sánchez, Marely; Albores Figueroa, Rosemberg; Montes Tapia, Fernando Félix; Gómez Danés, Luis Humberto (UANL. Facultad de Medicina, 2014)
Presently, there is controversy and misconception in the diagnosis and management of most congenital vascular malformations. The aim of this manuscript is to identify the current knowledge of these poorly understood and relatively uncommon pathologies. We will also review the updated terminology, classiication, pathogenesis, clinical presentation, diagnosis approach and management